PERAN USAHA MIKRO DALAM MENOPANG PEREKONOMIAN KELUARGA PADA MASA PANDEMI COVID-19 - Aye Sudarto (ANALISIS, 2021)
The role of ultra-mikro and small businesses in Metro City, especially in the campus cake market, which is located in the eastern part of the Mulyo Metro, is significant. So far, he has been able to survive and support the surrounding community. Producers and vendors meet at the cake market. Can develop and support the family during normal times as well as in times of crisis as it is today. The number of market snack producers in the campus cake market is 35 people and 22 traders are distributors of market snacks. The development of the campus cake market can be seen from the turnover, types of cakes and employment. The development of ultra mikro and mikro businesses is quite good. However, during the Covid 19 pandemic, there was a significant decrease in business.